Software Project Planning-Relationship between Project Planning and Project Success - Goel, Pragati; Jawale, Santosh (SFIMAR Research Review, 2011)
Due to an increasing market demands and a rapid expansion of technological possibilities, the pressure on the software industry is constantly growing. This paper aims at exploring the project planning paradigm in the software industry to answer questions like, How do software companies define project planning? What different factors influence the choice of planning strategy? What is necessary to do in order to become successful in the project planning? Does the software industry have exactly the same view regarding project planning? Do they include everything that, according to literature, should be included in a project plan? The study has been chosen to start with the project plan and what kind of parts that can be included in a project plan. This first part is project estimations, and this part is divided into why, what and how to estimate. Estimations are followed by risk planning. Risk planning is divided into risk concepts, risk identification, risk quantification and risk response planning. The last part has been chosen to present project planning management. This includes planning management, project organizational structure, process models, roles and responsibilities. All these parts have been identified from well recognized software engineering material.